2015
DOI: 10.1021/acssuschemeng.5b00405
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lignin Supramolecular Hydrogels with Mechanically Responsive and Self-Healing Properties

Abstract: The development of functional polymers from renewable lignin is attractive due to the depletion of fossil fuel and increasing environmental usage. A series of poly(ethylene glycol) methyl ether methacrylate (PEGMA)-grafted lignin hyperbranched copolymers were prepared by atom transfer radical polymerization (ATRP). The chemical structures, molecular characteristic and thermal properties of these copolymers were evaluated and such copolymers were prepared in a range of molecular weights from 38.7 to 65.0 kDa by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(98 citation statements)
references
References 55 publications
0
98
0
Order By: Relevance
“…Our group studied shear‐thinning and self‐healing properties of supramolecular hydrogels with different types of polymeric entities ,. Dynamic rheological studies confirmed that non‐covalent inclusion complexation renders the sol‐gel process reversible subjected to shear and heating/cooling cycles.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 93%
“…Our group studied shear‐thinning and self‐healing properties of supramolecular hydrogels with different types of polymeric entities ,. Dynamic rheological studies confirmed that non‐covalent inclusion complexation renders the sol‐gel process reversible subjected to shear and heating/cooling cycles.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 93%
“…Loh et al. furthermore prepared a series of PEGMA‐grafted lignin hyperbranched copolymers . The hyperbranched architecture formed supramolecular hydrogels with a very low critical gelation concentration of 1 wt % copolymers, in the presence of α‐CD (Figure ).…”
Section: Supramolecular Self‐assembled Structuresmentioning
confidence: 99%
“…Depending on the carbon numbers in the monomeric constituents, PHAs can be classified as short-chain-length PHAs (C 3 -C 5 ), which consists of 3-5 carbon monomers, and mediumchain-length PHAs (MCL-PHA, C 6 -C 14 ), which consists of 6-14 carbon monomers in the 3-hydroxyalkanoate units (Figure 1b). 3,4 For example, poly(3-hydroxybutyrate) (PHB), poly(3-hydroxyvalerate) (PHV) and their copolymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) are typical examples of short-chain-length PHAs, whereas poly(3-hydroxyoctanoate) (PHO) and poly(3-hydroxynonanoate) (PHN), which are primarily formed as copolymers with 3-hydroxyhexanoate (HHx), 3-hydroxyheptanoate (HH) and/or 3-hydroxydecanoate (HD), are typical examples of MCL-PHAs. More than 150 different PHA monomers have been identified, which renders them the largest group of natural polyesters.…”
Section: Introductionmentioning
confidence: 99%